2022
DOI: 10.1093/jas/skac256
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals candidate genes of the synthesis of branched-chain fatty acids related to mutton flavor in the lamb liver using Allium mongolicum Regel extract

Abstract: The objective of this study was to identify candidate genes via which Allium Mongolicum Regel ethanol extract (AME) affects the synthesis of branched-chain fatty acids (BCFAs) related to mutton flavor by transcriptome analysis in the lamb liver. Thirty male Small-tailed Han sheep (3 months old; 33.6 ± 1.2 kg) were randomly divided into two groups and fed for 75 days with a basal diet containing no AME (CON, control group) or 2.8 g·lamb -1·d -1 AME (AME group). Twelve sheep, CON (n=6) and AME (n=6), were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In recent years, the integration of different omics technologies to explain changes in food quality on a molecular basis has been implemented in various research areas such as systems microbiology ( Fondi and Liò, 2015 ), food and nutritional science ( Kato et al, 2011 ), disease biology ( Pathak and Davé, 2014 ), and meat science ( Lim et al, 2017 ; Ma et al, 2020 ; Windarsih et al, 2022 ; Yan et al, 2021 ). Although successful integration has not yet been realized in meat science research, studies have been conducted by integrating transcriptomics and proteomics ( Lim et al, 2017 ; Yan et al, 2021 ; Zhang et al, 2022c ; Zhao et al, 2022b ), proteomics and metabolomics ( Ma et al, 2020 ; Windarsih et al, 2022 ), and transcriptomics and metabolomics ( Chen et al, 2022 ; Cui et al, 2023 ; Wu et al, 2020 ; Zhang et al., 2022d ).…”
Section: Multi-omics Approach To Improve Meat Quality and Taste Chara...mentioning
confidence: 99%
“…In recent years, the integration of different omics technologies to explain changes in food quality on a molecular basis has been implemented in various research areas such as systems microbiology ( Fondi and Liò, 2015 ), food and nutritional science ( Kato et al, 2011 ), disease biology ( Pathak and Davé, 2014 ), and meat science ( Lim et al, 2017 ; Ma et al, 2020 ; Windarsih et al, 2022 ; Yan et al, 2021 ). Although successful integration has not yet been realized in meat science research, studies have been conducted by integrating transcriptomics and proteomics ( Lim et al, 2017 ; Yan et al, 2021 ; Zhang et al, 2022c ; Zhao et al, 2022b ), proteomics and metabolomics ( Ma et al, 2020 ; Windarsih et al, 2022 ), and transcriptomics and metabolomics ( Chen et al, 2022 ; Cui et al, 2023 ; Wu et al, 2020 ; Zhang et al., 2022d ).…”
Section: Multi-omics Approach To Improve Meat Quality and Taste Chara...mentioning
confidence: 99%
“…The results showed that MYOD1 inhibited the adipogenic differentiation of skeletal myosatellite cells and promoted the differentiation of muscle cells and myotube formation. Zhao et al (2022) [36] found that the levels of 4-methyloctanoic acid and 4-methylnonanoic acid in lambs fed scallions were significantly lower than those in the control group, resulting in a significant reduction in mutton odor. Transcriptomics analysis showed that the pathways involved were glutathione metabolism, extracellular matrix receptor interaction and steroid hormone biosynthesis.…”
Section: Effects Of Different Feeding Managements On Imf Depositionmentioning
confidence: 99%
“…As of now, there are many transcriptomic studies on wool ( 14 ), muscle ( 15 ) and liver ( 16 ) in other sheep breeds, including sheep, cashmere goat and small-tailed Han sheep. However, no transcriptomic studies have been conducted on Ganxi goats, and no bioinformatics studies have been conducted on the mechanism of cuproptosis-related genes in wound healing.…”
Section: Introductionmentioning
confidence: 99%